Tear Break Up Time Pattern in Medical Students After COVID-19 Pandemic - SUDIBIA, NI KADEK PUSPA MEGA PUTRI; Handayani, Ariesanti Tri (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesCOVID-19 pandemic makes most activities are carried out online with using the VDT. Tear Break UpTime (TBUT) examination is a short and fast examination and is able to determine damage to thetear film and subjective examination using the OSDI Questionnaire. This study aimed to assess TBUTpattern in medical students after COVID-19 pandemic regarding VDT used for online learningactivities. MethodsThis study is an observational analytic study with a cross-sectional approach. The difference inproportion between TBUT results based on gender was analyzed using chi-square test. Statisticalanalysis was carried out using a multivariate test based on the results of data normality. The onewayANOVA test is used for normally distributed data, while Kruskall-Wallis is used if the data is notnormally distributed. ResultsA total of 75 subjects were included in the study, consisting of 53 females (70,7%) and 22 males(29.3%). Average use of VDT 8 hours per day. The average TBUT in both eyes were < 10 secondsand random breaks was the most common pattern seen in this study (61,3% OD and 62,7% OS).There was no significant difference between TBUT and gender but there was statistically significantdifference between OSDI score and TBUT. ConclusionLongterm use of VDT may be affect TBUT and subjective symptoms shown by OSDI score. Randombreak was the most common pattern seen in young adults in relation with VDT use.